2020
DOI: 10.1186/s12989-020-00369-9
|View full text |Cite
|
Sign up to set email alerts
|

Particle characterization and toxicity in C57BL/6 mice following instillation of five different diesel exhaust particles designed to differ in physicochemical properties

Abstract: Background: Diesel exhaust is carcinogenic and exposure to diesel particles cause health effects. We investigated the toxicity of diesel exhaust particles designed to have varying physicochemical properties in order to attribute health effects to specific particle characteristics. Particles from three fuel types were compared at 13% engine intake O 2 concentration: MK1 ultra low sulfur diesel (DEP13) and the two renewable diesel fuels hydrotreated vegetable oil (HVO13) and rapeseed methyl ester (RME13). Additi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 85 publications
1
28
0
Order By: Relevance
“…RME is one type in the group of fatty-acid methyl ester (FAME) biodiesel fuels. The motivation for the choice of the test fuels was that substituting fossil diesel by renewable diesel fuels, such as HVO and FAME-type biodiesel, to mitigate CO 2 emissions, changes the physicochemical characteristics of the diesel engine exhaust emissions (Dimitriadis et al, 2018;Giakoumis et al, 2012;Gren et al, 2020;Karavalakis et al, 2017;Murtonen et al, 2010). Using the HVO and FAME-type fuels can significantly reduce PM, HC, and CO emissions in diesel exhaust (Giakoumis et al, 2012;McCaffery et al, 2020) and change the particle size distribution and soot nanostructure (Lapuerta et al, 2008;Savic et al, 2016) in comparison to fossil diesel fuel.…”
Section: Experiments Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…RME is one type in the group of fatty-acid methyl ester (FAME) biodiesel fuels. The motivation for the choice of the test fuels was that substituting fossil diesel by renewable diesel fuels, such as HVO and FAME-type biodiesel, to mitigate CO 2 emissions, changes the physicochemical characteristics of the diesel engine exhaust emissions (Dimitriadis et al, 2018;Giakoumis et al, 2012;Gren et al, 2020;Karavalakis et al, 2017;Murtonen et al, 2010). Using the HVO and FAME-type fuels can significantly reduce PM, HC, and CO emissions in diesel exhaust (Giakoumis et al, 2012;McCaffery et al, 2020) and change the particle size distribution and soot nanostructure (Lapuerta et al, 2008;Savic et al, 2016) in comparison to fossil diesel fuel.…”
Section: Experiments Setupmentioning
confidence: 99%
“…Diesel emissions, especially from old vehicles without emission aftertreatment systems such as DPF or DOC, can severely impair air quality in urban areas and thus adversely affect human health. Both the properties of the solid core particles and carcinogenic components adsorbed to the particles may affect the adverse effects (Bové et al, 2019;Bendtsen et al, 2020). These effects of diesel combustion emissions are known; however, their total indirect climate effect, including the potential of diesel emission particles to act as INPs, remains less studied.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review reported several in vitro studies linking HVO exhaust to oxidative stress, inflammation and genotoxicity, whereas animal studies did not indicate genotoxicity in lung tissue [ 9 ]. Bendtsen et al found that the toxicity of HVO and petroleum diesel in mice were similar, but depended largely on engine conditions; higher reactive oxygen species (ROS) formation and more DNA strand breaks were linked to engine conditions that favored high combustion temperatures [ 5 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, growing evidence suggests that deposited or retained particle (NM) surface area normalized to lung mass can be leveraged to unify in vivo inflammation data from mice and rats, based on PMN numbers normalized to total cell numbers in the BALF, and to identify distinct classes of NM. Representatives of some of the different NM classes include titanium dioxide (TiO 2 ) [12,13], multiwall carbon nanotubes (MWCNTs) [14][15][16], nano-ceria [17], granular biodurable particles and transition metal oxides [12,[18][19][20], diesel exhaust particles [21], nanoclays [22], and halloysite nanotubes [23].…”
mentioning
confidence: 99%